Hadith #257 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
I heard Abu Huraira saying that the Messenger of Allah (ﷺ) observed: people will certainly ask you about everything till they will propound: Allah created every thing, but who created Allah?
Grade: Sahih

Hadith #3331 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
Maimuna daughter of al-Harith narrated to me that Allah’s Messenger (ﷺ) married her and he was not in the state of Ihram. And she (Maimuna) was my mother’s sister and that of Ibn ‘Abbas (Allah be pleased with them).
Grade: Sahih

Hadith #4553 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
If I had not the fear of committing (sin) for concealing the knowledge I would not have written to him. Najda wrote to him saying (after praising the Almighty and invoking blessings on the Prophet): Tell me whether the Messenger of Allah (ﷺ) took women to participate with him in Jihad; (if he did), whether he allotted them a regular share from the booty; whether he killed the children of (the enemy in the war), how long an orphan would be entitled to consideration as such, and for whom the Khu
Grade: Sahih

Hadith #4555 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
Najda b. ‘Amir al-Haruri wrote to Ibn Abbas asking him about the slave and the woman as to whether they would get a share from the booty (it they participated in Jihad) ; about the killing of (enemy) children (in war) ; about the orphan as to when his orphanhood comes to an end; about kinsmen (of the Holy Prophet) as to who they are. He said to Yazid: Write to him. (If he were not likely to fall into folly, I would not have written to him.) Write: You have written asking about the woman and th
Grade: Sahih

Hadith #4904 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
A newly wedded person of Medina invited us to a wedding feast, and he served us thirteen lizards. There were those who ate it and those who abandoned it. I met Ibn ‘Abbas the next day, and informed him (about this) in the presence of many persons. Some of them said that the Messenger of Allah (ﷺ) had observed: I neither eat it nor forbid (anyone) from eating it, nor declare it to be unlawful. Thereupon Ibn ‘Abbas said: Sad it is what you say! Allah’s Apostle (ﷺ) has not been sent, but
Grade: Sahih

Hadith #5481 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
Abu Sa’id said: So I stood up, and went to ‘Umar and gave witness (to what Abu Musa had said).
Grade: Sahih

Hadith #6067 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
Zaid. you have been able to acquire a great virtue that you saw Allah’s Messenger (ﷺ) listened to his talk, fought by his side in (different) battles, offered prayer behind me. Zaid, you have in fact earned a great virtue. Zaid, narrate to us what you heard from Allah’s Messenger (ﷺ). He said: I have grown old and have almost spent my age and I have forgotten some of the things which I remembered in connection with Allah’s Messenger (ﷺ), so accept whatever I narrate to you, and which
Grade: Sahih

Hadith #6070 - Sahih Muslim - Yazid bin 'Abdul 'Aziz bin Siyah يزيد بن عبد العزيز بن سياه (Sahih Muslim)
We went to him (Zaid b. Arqam) and said to him. You have found goodness (for you had the honour) to live in the company of Allah’s Messenger (ﷺ) and offered prayer behind him, and the rest of the hadith is the same but with this variation of wording that lie said: Behold, for I am leaving amongst you two weighty things, one of which is the Book of Allah, the Exalted and Glorious, and that is the rope of Allah. He who holds it fast would be on right guidance and he who abandons it would be in
Grade: Sahih